2020
DOI: 10.1002/adfm.202007624
|View full text |Cite
|
Sign up to set email alerts
|

Mixed‐Metal MOF‐74 Templated Catalysts for Efficient Carbon Dioxide Capture and Methanation

Abstract: The vast chemical and structural tunability of metal–organic frameworks (MOFs) are beginning to be harnessed as functional supports for catalytic nanoparticles spanning a range of applications. However, a lack of straightforward methods for producing nanoparticle‐encapsulated MOFs as efficient heterogeneous catalysts limits their usage. Herein, a mixed‐metal MOF, NiMg‐MOF‐74, is utilized as a template to disperse small Ni nanoclusters throughout the parent MOF. By exploiting the difference in NiO and MgO coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 68 publications
2
39
0
Order By: Relevance
“…[21][22][23] These processing steps result in loss of organic linkers that offer the ability to confine the size and tune the electronic properties of nanocrystals grown inside the MOFs. [24][25][26] We posit that if we were able to devise a method to construct nanomaterials from MOFs while keeping the organic linker unaltered, we would have the opportunity to use it to stabilize the as-formed active sites under CO2RR operating conditions. Herein, we report an electrochemical oxidation-reduction (EOR) approach for the preparation of sub-nanometer Cu clusters from Cu-based MOFs that retains the organic linkers for highly selective and durable electrosynthesis of methane during CO2RR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] These processing steps result in loss of organic linkers that offer the ability to confine the size and tune the electronic properties of nanocrystals grown inside the MOFs. [24][25][26] We posit that if we were able to devise a method to construct nanomaterials from MOFs while keeping the organic linker unaltered, we would have the opportunity to use it to stabilize the as-formed active sites under CO2RR operating conditions. Herein, we report an electrochemical oxidation-reduction (EOR) approach for the preparation of sub-nanometer Cu clusters from Cu-based MOFs that retains the organic linkers for highly selective and durable electrosynthesis of methane during CO2RR.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] These processing steps result in loss of organic linkers that offer the ability to confine the size and tune the electronic properties of nanocrystals grown inside the MOFs. [24][25][26] We posit that if we were able to devise a method to construct nanomaterials from MOFs while keeping the organic linker unaltered, we would have the opportunity to use it to stabilize the as-formed active sites under CO 2 RR operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…72 The pore structures of MOFs separates the UMNPs one from another, which can avoid the aggregation of UMNPs during the catalytic process. 73,74 The synthesis and application of MOFs is a current hot research field, and many new MOF structures are reported every year, but not all MOFs are suitable for the synthesis of UMNPs and their application in catalysis. For example, when H 2 O is generated or participates in the catalytic reaction pathway, the framework of MOF-177 can easily decompose and collapse.…”
Section: Mofsmentioning
confidence: 99%
“…Carbon capture and storage (CCS) has evolved as a promising strategy, [3–5] in which developing high‐efficiency CO 2 capture and separation materials is the crucial prerequisite [6–8] . Metal‐organic frameworks (MOFs) have attracted extensive interest due to their large surface area, abundant metal sites, and easy functionalization [9–11] . Numerous strategies such as doping, functionalization, and pore topological design have been adopted to improve the CO 2 capture and separation performance [12–14] …”
Section: Introductionmentioning
confidence: 99%